Fate of micropollutants during the advanced treatment of sewage sludge: degradation of triclosan, ciprofloxacin, and oxytetracycline - Mercan, Nazire. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2015., 2015)
Antimicrobials are emerging organic contaminants that enter wastewater network as consequence of human activities. In contrast to other emerging organic contaminants, antimicrobials have the potential to cause a secondary pollution. In order to eliminate the environmental risk of both antimicrobial and antimicrobial resistance bacteria pollution the treatment of these contaminants in sewage sludge could be necessary. Considering these facts, the fate of a model antimicrobial Triclosan (TCS) in waste secondary sewage sludge was investigated during the application of heat and ferrous iron activated persulfate process. An experimental design methodology was applied for this thermochemical process to evaluate the combined effects of selected parameters. The degradation rate of TCS was >99.9% with 22.7 mM dose of persulfate and 0.5 molar ratios of Fe2+/S2O8 2– at 75 °C in 90 min treatment period. While increasing dose of persulfate and temperature have positive influence on TCS degradation higher dose of Fe2+ reduced the treatment efficiency of the process. However, the addition of iron to persulfate process shortened the treatment period required for effective antimicrobial degradation, enhanced the solubilisation of sludge constituents, and caused a reduction in Adsorbable orgnic halogens (AOX) values of sludge by providing both sulphate and hydroxyl radicals in the sludge. The beneficial effects of iron addition in persulfate process were not limited with these it also provided the recovery of phosphorous in the solid phase of the sludge and slight improvement in sludge dewaterability. Activation of persulfate with microwave (MW) irradiation resulted in lower extractable protein in the sludge than that obtained by Heat/Fe2+/S2O8 2- treatment.
Keywords: Anti-infective agents.